2014
DOI: 10.1080/10538720.2014.891452
|View full text |Cite
|
Sign up to set email alerts
|

Pathways Connecting Sexual Minority Stressors and Psychological Distress Among Lesbian Women

Abstract: Mechanisms underlying the relationship between proximal sexual minority stressors and psychological distress among selfidentified lesbian women are examined. Structural equation modeling demonstrated that stigma consciousness and concealment of one's sexual orientation were indirectly associated with psychological distress via increased difficulty talking with others about sexual orientation (i.e., social constraints) and brooding as sequential mediating variables. These findings suggest that lesbian women's c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 41 publications
0
31
1
Order By: Relevance
“…Overall, findings supported our hypotheses that these resources serve as indirect mechanisms explaining how proximal minority stress links with health. Findings contribute to the limited work on mechanisms between minority stress and outcomes (e.g., Lehavot and Simoni, ; Lewis et al., ; Mereish & Poteat, ). That minority stress is negatively related to psychosocial resources may be especially important given resources are supposed to help individuals cope with stress (Meyer, ).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Overall, findings supported our hypotheses that these resources serve as indirect mechanisms explaining how proximal minority stress links with health. Findings contribute to the limited work on mechanisms between minority stress and outcomes (e.g., Lehavot and Simoni, ; Lewis et al., ; Mereish & Poteat, ). That minority stress is negatively related to psychosocial resources may be especially important given resources are supposed to help individuals cope with stress (Meyer, ).…”
Section: Discussionmentioning
confidence: 63%
“…Lehavot and Simoni () found that social support and spirituality mediated the relation between minority stress (victimization, internalized heterosexism, and concealment due to gender expression ranging from femininity/feminine to masculinity/butch) and mental health and substance use in sexual minority women. Lewis and colleagues found that social constraints and rumination mediated proximal minority stress and psychological distress (Lewis, Milletich, Mason, & Derlega, ), and social constraints, isolation, and coping indirectly explained minority stress and alcohol use (Lewis, Winstead, Mason, & Lau‐Barraco, ) in lesbian women. Puckett, Levitt, Horne, and Hayes‐Skelton () reported that self‐criticism and lack of connectedness to sexual minorities mediated internalized heterosexism and psychological distress.…”
Section: General Psychosocial Resources Explaining Sexual Minority Stmentioning
confidence: 99%
“…Brooding rumination-a maladaptive coping style of emotion regulation marked by repetitive, self-focused thoughts-acts as one pathway through which stigma negatively affects health (Hatzenbuehler, Nolen-Hoeksema, & Dovidio, 2009). Past research has found that rumination is highly correlated with psychological distress (Lewis, Milletich, Mason, & Derlega, 2014), specifically depressive symptomology, both cross-sectionally, and as a cross-lagged predictor (Moberly & Watkins, 2008;Treynor, Gonzalez, & Nolen-Hoeksema, 2003). In addition, increased brooding rumination has been strongly connected to worse physical health (Ottaviani et al, 2016;Sansone & Sansone, 2012), likely through the increased wear and tear of an extended somatic stress response (Verkuil, Brosschot, Gebhardt, & Thayer, 2010).…”
Section: Brooding Ruminationmentioning
confidence: 99%
“…While most people engage in this form of passive coping at least some of the time (Moberly & Watkins, 2008;Treynor et al, 2003), previous research has shown that stigmatized individuals ruminate at a greater rate than their nonstigmatized peers (Timmins, Rimes, & Rahman, 2017). Moreover, for these individuals, brooding rumination appears to be a common response to stigma-related stress (Hatzenbuehler et al, 2009;Lewis et al, 2014).…”
Section: Brooding Ruminationmentioning
confidence: 99%
See 1 more Smart Citation